Development and Validation of a Scoring System for Predicting Clinical Coronary Artery Perforation During Percutaneous Coronary Interventions of Chronic Total Occlusions: The PROGRESS-CTO Perforation Score - Kostantinis, Spyridon; Simsek, Bahadir; Karacsonyi, Judit; Alaswad, Khaldoon; Jaffer, Farouc; Khatri, Jaikirshan; Choi, James; Jaber, Wissam; Rinfret, Stephane; Nicholson, William; Patel, Mitul; Mahmud, Ehtisham; et al. (ELSEVIER SCIENCE INC, 2022)
34th Annual Symposium on Transcatheter Cardiovascular Therapeutics (TCT), Boston, MA, SEP 16-19, 2022